Comparative Genetic Analysis of Mycobacterium ulcerans and Mycobacterium marinum Reveals Evidence of Recent Divergence - Stinear, Timothy P. (American Society for Microbiology, 2000)
Previous studies of the 16S rRNA genes from Mycobacterium ulcerans and Mycobacterium marinum have suggested a very close genetic relationship between these species (99.6% identity). However, these organisms are phenotypically distinct and cause diseases with very different pathologies. To investigate this apparent paradox, we compared 3,306 nucleotides from the partial sequences of eight housekeeping and structural genes derived from 18 M. ulcerans strains and 22 M. marinum strains. This analysis confirmed the close genetic relationship inferred from the 16S rRNA data, with nucleotide sequence identity ranging from 98.1 to 99.7%. The multilocus sequence analysis also confirmed previous genotype studies of M. ulcerans that have identified distinct genotypes within a geographical region. Single isolates of both M. ulcerans and M. marinum that were shown by the sequence analysis to be the most closely related were then selected for further study. One- and two-dimensional pulsed-field gel electrophoresis was employed to compare the architecture and size of the genome from each species. Genome sizes of approximately 4.4 and 4.6 Mb were obtained for M. ulcerans and M. marinum, respectively. Significant macrorestriction fragment polymorphism was observed between the species. However, hybridization analysis of DNA cleaved with more frequently cutting enzymes identified significant preservation of the flanking sequence at seven of the eight loci sequenced. The exception was the 16S rRNA locus. Two high-copy-number insertion sequences, IS2404 and IS2606, have recently been reported in M. ulcerans, and significantly, these elements are not present in M. marinum. Hybridization of the AseI restriction fragments from M. ulcerans with IS2404 and IS2606 indicated widespread genome distribution for both of these repeated sequences. Taken together, these data strongly suggest that M. ulcerans has recently diverged from M. marinum by the acquisition and concomitant loss of DNA in a manner analogous to the emergence of M. tuberculosis, where species diversity is being driven mainly by the activity of mobile DNA elements.